2013 BASIC CURRICULUM EDUCATION PROTOTYPE MODEL LEARNING - Samsudin, Samsudin; Sudarso, Sudarso; Khaeroni, Khaeroni (Program Pascasarjana Universitas Negeri Jakarta, 2018)
This research and development aims to produce a locomotor-based basic motion learning model for elementary school children. Specifically this study aims to: 1) Produce products based on locomotor basic motion learning models for elementary school children; 2) Test the effectiveness of locomotor-based basic motion learning models for elementary school children. The research method used in this research is the research and development method of Borg and Gall. Pretest and Posttest Exploitation Tests aim to find out whether there is an increase. The research conclusion is stated to be significant if t count> t table at 5% significance level and p <0.05. The average pretest score of the experimental group was 6.15 and the average posttest score was 9.95. so it has increased in the locomotor base motion of 3,800, t count> t table at 5% significant level (33,230> 2,042) and has a p value of 0.00 <0,05 which means it can be concluded that there is a significant increase in the results of basic motion in the experimental group . Pretest t test and posttest control aims to find out whether there is an increase. The research conclusion is stated to be significant if t count> t table at 5% significance level and p <0.05. The average value of the pretest of the control group was 6.1 and the average posttest score was 7.75 so that it increased in the locomotor basic motion of 1.65, t count> t table at a significant level of 5% (9,927> 2,042) and had a p value of 0,000 <0,05 which means it can be concluded that there is a significant increase in the results of basic motion in the control group. Furthermore, to see the effect of treatment based on its significance is to use a statistical test using a mean difference test of two independent meanings. Analysis of independent-sample t-test on the posttest of the experimental class and posttest of the control group aims to find out whether there is a significant difference in posttest scores in the experimental group and the control group. The research conclusion is stated to be significant if t count> t table at 5% significance level and p <0.05. Summary of posttest test, it is known that the average locomotor basic motion of the experimental group is 9.95 and the average locomotor base motion of the control group is 7.75. So that it can be concluded that the average locomotor basic motion of the experimental group 2.5 is better than the control group. It is known that t count is 9,515 with a significant 0.002. T table obtained from db 78 at a significant level of 5% is 1.671 so the value of t count> t table (9,515> 1,671). And it was concluded that there was a significant and effective influence for elementary school children.   Keywords: basic, scientific motion